Acoustics of courtrooms in Portugal - António P. O. Carvalho (2003)
This paper presents the results of field measurements in 29 courtrooms in Portugal (average volume of 440 m3) regarding their acoustic behavior to several objective parameters: (RT, EDT, C80, D50, TS, RASTI and Dn,w). The individual results show, for instance, that the mean measured values in each room for RASTI were from 0.39 to 0.74 (with a global mean value of 0.53 for all rooms) and for the RT (500/1k Hz) were from 0.5 to 3.6 s (with a global mean of 1.6 s for all rooms). The evaluation of the airborne sound isolation index (Dn,w) between courtroom and main lobby found values from 17 to 30 dB. These results show an insufficient acoustical behavior for almost all these courtrooms. Two groups of rooms were formed regarding their date of construction: